Is Neurosurgery With Adjuvant Radiotherapy an Effective Treatment Modality in Isolated Brain Involvement From Endometrial Cancer?: From Case Report to Analysis. Issue 2 (1st February 2017) - Kimyon, Gunsu; Turan, Taner; Basaran, Derman; Turkmen, Osman; Karalok, Alper; Tasci, Tolga; Tulunay, Gokhan; Kose, Mehmet Faruk
Abstract : Aim: The aim of this study was to evaluate the treatment options and post–brain involvement survival (PBIS) of patients with isolated brain involvement from endometrial cancer (EC). Materials and Methods: The literature electronic search was conducted from 1972 to May 2016 to identify articles about isolated (without extracranial metastases) brain involvement from EC at recurrence and the initial diagnosis. Forty-eight articles were found. After comprehensive evaluation of case series and case reports, the study included 49 cases. Results: The median age of the patients at initial diagnosis was 57 years (range, 40–77 years). Poor differentiation was determined in 36 (73.5%) patients. Thirty-five (71.4%) patients had a single brain lesion. Lesion was found in the supratentorial part of the brain in 33 (67.3%) patients. Median PBIS for all cohorts was 13 months (range, 0.25–118 months) with 2-year PBIS of 52% and 5-year PBIS of 37%. Age, tumor type, grade, disease-free interval, diagnosis time of brain lesion, localization, and number of brain lesion were not predictive of PBIS. Two-year PBIS was 77% in patients who underwent surgical resection and radiotherapy, whereas it was 19% in the surgical resection–only group, and 20% in the primary radiotherapy–only group ( P s = 0.003 and 0.001, respectively). Chemotherapy was not associated with improved PBIS. Conclusions: Although neuroinvasion from EC appears mostly with a disseminated disease, there is a considerable amount of patients with isolated brain involvement who would have a higher chance of curability. Surgery with radiotherapy is the rational current management option, and this improves the survival for isolated brain involvement from EC.